„Pracujemy dla Polski” : listy Władysława Platera do Józefa Ignacego Kraszewskiego z lat 1863-1887 - Pietrzyk, Zdzisław (2022)
The correspondence of Józef Ignacy Kraszewski kept in the Manuscript Section of the Jagiellonian Library constitutes an indispensable source for the history of Polish culture in the second half of the 19th century. The collection of Władysław Plater’s letters is remarkable among hundreds of Kraszewski’s correspondents. These letters were written in the years 1863-1887, so they include relations from almost a quarter of the century of activities characterising the founder of the Polish National Museum in Rapperswil.